Late complications of transcatheter closure of patent foramen ovale: new technology and new outcomes. (September 2009) - Staubach, Stephan; Bertog, Stefan; Wunderlich, Nina; Sievert, Horst
As a method to prevent recurrent paradoxical embolism and therefore cryptogenic stroke, catheter-based patent foramen ovale closure was first reported in 1992. Since then numerous different devices have been designed to prevent paradoxical embolism. The development of new devices has risen pretty rapidly. Currently, no device can be regarded as the gold standard. Prospective randomized trials comparing interventionalpatent foramen ovale closure with medical treatment are still lacking. The primary aim is to create a device which is easy to implant and able to prevent paradoxical embolism. Additional goals are to minimize early and late complications, such as thrombembolism, erosion of adjacent structures, thrombus formation or atrial arrhythmia. This review gives an overview of the data and the current literature regarding long-term complications (follow-up ≥≥ 1 month) after patent foramen ovale closure with current devices and presents the initial, midterm and late results after patent foramen ovale closure with newer devices.